Structural Model of Work-Life Balance Effect on Nurse Work Engagement - Rita Markus Idulfilastri; Rosyeni Chan; Dhindayanti Putri (Jurnal Keperawatan, 2021)
Introduction: High job demands can cause problems for nurses, increased stress levels, burnout, and even turnover which results in decreased performance. Conditions of work-life balance that are not aligned may reduce work attachments. Objectives: to examine the structural model of the effect of work-life balance on work engagement. Methods: The research participants were 120 nurses, diploma graduates or nurses who were actively working in the field of nursing and living with their families. Data were obtained by using the UWES-9 questionnaire and the Industrial Society's Work-Life. Data processing used the Structural Equation Modelling (SEM) method, namely testing the measurement model with Confirmatory Factor Analysis (CFA) and testing the structural model with SEM methods with the LISREL 8.8.0 program. Results: The structural model produces a work-life balance of 8 valid items, 3 valid items to the vigor dimension, 3 valid items dedication dimension and 2 valid items absorption dimensions. Work-life balance as a predictor has an effect on work attachment but is still weak (γ = 0.29; sig; R2 = 8%). The work-life of nurses is not yet balanced and it is proven that nurses find it difficult to find time to relax, and maintain relationships with friends and relatives. Nurses perceive their work as very meaningful and it is proven by their strong dedication. Conclusions: The structural model has a fit model, that work-life balance is still weak and has not been able to influence work engagement. Nurses work because of their strong dedication to their work.